PEMETAAN KEBUTUHAN DAN POTENSI DESA MEDALSARI DENGAN ANALISIS SWOT SEBAGAI DASAR PERENCANAAN PENGABDIAN MASYARAKAT - Mursita, Rohmah Ageng; Asshidiqy, Ahmad Rifqy; Yuniarti, Puji; Nurmalinda, Rossa; Annur, Siti Ayu Jahrotun Nisa (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACT Medalsari Village, Pangkalan District, Karawang Regency, has great potential in social, economic, and cultural aspects that can be developed through community service based on real needs. The mapping identifies two main needs: child development education and strengthening creative economy through MSMEs. This program aims to enhance the capacity of village women in child care and household economic management, while also strengthening village self-reliance. The implementation method uses a participatory approach through stages of observation, interviews, Focus Group Discussions (FGD), training, mentoring and pre-test and post-test evaluation. Activities include parenting education (positive parenting, balanced nutrition, child development stimulation), MSME training (production based on local potential, business management, business legality through NIB, branding and packaging), and product exhibitions. A SWOT analysis was used to map strengths, weaknesses, opportunities, and threats, as well as to formulate sustainability strategies. The results show a significant increase in mothers' knowledge regarding child development, creative economic skills, and awareness of business legality. Village MSME products were successfully developed with more attractive branding and packaging, and promoted through local exhibitions. In addition, a need for higher education literacy was identified, particularly information on admission pathways and scholarships, to motivate mothers to encourage their children to pursue university studies. Overall, this community service program contributed to enhancing mothers’ capacity in child-rearing, creative economic empowerment, and awareness of higher education. The synergy of these three focuses is expected to create a holistic and sustainable community empowerment ecosystem in Medalsari Village, oriented toward improving quality of life and village self-reliance. ABSTRAK Desa Medalsari, Kecamatan Pangkalan, Kabupaten Karawang, memiliki potensi besar dalam aspek sosial, ekonomi, dan budaya yang dapat dikembangkan melalui pengabdian masyarakat berbasis kebutuhan riil. Pemetaan mengidentifikasi dua kebutuhan utama: edukasi tumbuh kembang anak dan penguatan ekonomi kreatif berbasis UMKM. Program ini bertujuan meningkatkan kapasitas ibu-ibu desa dalam pengasuhan anak dan pengelolaan ekonomi rumah tangga, sekaligus memperkuat kemandirian desa. Metode pelaksanaan menggunakan pendekatan partisipatif dengan tahapan observasi, wawancara, Focus Group Discussion (FGD), pelatihan, pendampingan, serta evaluasi pre-test dan post-test. Kegiatan meliputi edukasi parenting (pola asuh positif, gizi seimbang, stimulasi perkembangan anak), pelatihan UMKM (produksi berbasis potensi lokal, manajemen usaha, legalitas usaha melalui NIB, serta branding dan pengemasan), hingga pameran produk. Analisis SWOT digunakan untuk memetakan kekuatan, kelemahan, peluang, dan ancaman, sekaligus merumuskan strategi keberlanjutan. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada pengetahuan ibu-ibu mengenai tumbuh kembang anak, keterampilan ekonomi kreatif, serta kesadaran pentingnya legalitas usaha. Produk UMKM desa berhasil dikembangkan dengan merek dan kemasan lebih menarik serta dipromosikan melalui pameran lokal. Selain itu, teridentifikasi kebutuhan literasi pendidikan tinggi, terutama informasi jalur masuk dan beasiswa, untuk memotivasi ibu-ibu mendorong anak melanjutkan studi ke perguruan tinggi. Secara keseluruhan, program pengabdian ini berkontribusi pada peningkatan kapasitas ibu-ibu dalam pengasuhan anak, pemberdayaan ekonomi kreatif, serta kesadaran pendidikan tinggi. Sinergi ketiga fokus tersebut diharapkan mampu membentuk ekosistem pemberdayaan masyarakat Desa Medalsari yang holistik, berkelanjutan, dan berorientasi pada peningkatan kualitas hidup serta kemandirian desa.